Effect of β-Hydroxybutyrate on Autophagy Dynamics During Severe Hypoglycemia and the Hypoglycemic Coma - Torres-Esquivel, Carmen; Montiel, Teresa; Flores-Méndez, Marco; Massieu, Lourdes (Frontiers in Cellular Neuroscience, 2020)
Glucose supply from blood is mandatory for brain functioning and its interruption during acute hypoglycemia or cerebral ischemia leads to brain injury. Alternative substrates to glucose such as the ketone bodies (KB), acetoacetate (AcAc) and β-hydroxybutyrate (BHB), can be used as energy fuels in brain during hypoglycemia and prevent neuronal death, but the mechanisms involved are still not well understood. During glucose deprivation adaptive cell responses can be activated such as autophagy, a lysosomal-dependent degradation process, to support cell survival. However, impaired or excessive autophagy can lead to cell dysfunction. We have previously shown that impaired autophagy contributes to neuronal death induced by glucose deprivation in cortical neurons and that D-BHB reestablishes the autophagic flux increasing viability. Here we aimed to investigate autophagy dynamics in the brain of rats subjected to severe hypoglycemia (SH) without glucose infusion (GI), severe hypoglycemia followed by GI (SH+GI) and to a brief period of hypoglycemic coma followed by GI (Coma). The effect of D-BHB administration after the coma was also tested (Coma+BHB). The transformation of LC3-I to LC3-II and the abundance of autophagy proteins, Beclin 1 (BECN1), ATG7 and ATG12–ATG5 conjugate, were analyzed as an index of autophagosome formation, and the levels of sequestrosome1/p62 (SQSTM1/p62) were determined as a hallmark of autophagic degradation. Data suggest that autophagosomes accumulate in the cortex and the hippocampus of rats after SH, likely due to impaired autophagic degradation. In the cortex, autophagosome accumulation persisted at 6 h after GI in animals exposed to SH but recovered basal levels at 24 h, while in the hippocampus no significant effect was observed. In animals subjected to coma, autophagosome accumulation was observed at 24 h after GI in both regions. D-BHB treatment reduced LC3-II and SQSTM1/p62 content and reduced ULK1 phosphorylation by AMPK, suggesting it stimulates the autophagic flux and decreases AMPK activity reducing autophagy initiation. D-BHB also reduced the number of degenerating cells. Together, data suggest different autophagy dynamics after GI in rats subjected to SH or the hypoglycemic coma, and support that protection by D-BHB is related to the reestablishment of functional autophagy and decreased autophagy initiation.